Program development of a preceptor bootcamp for operational pharmacy preceptors. (17th January 2020) - Smith, Devlin V; Gautreaux, Stefani; Gulbis, Alison M; Bruno, Jeffrey J; Garey, Kevin; Roux, Ryan K; Varkey, Divya
Abstract: Purpose: To describe the development, design, and implementation of a pilot preceptor development bootcamp and feedback related to its feasibility and impact on operational pharmacy preceptors. Summary: The University of Texas MD Anderson Cancer Center designed and implemented a pilot preceptor development bootcamp for operational staff pharmacists serving as residency preceptors for longitudinal weekend staffing experiences. A systematic, multipronged approach was taken to identify preceptor development gaps and design a full-day bootcamp curriculum. The resultant curriculum was comprised of content in major functional areas including using the 4 preceptor roles, documenting performance, giving and receiving feedback, and dealing with difficult situations or learners. The impact of the pilot preceptor development bootcamp was assessed using survey methodology and qualitative feedback from debrief discussions. Conclusion: Implementation of a pilot preceptor bootcamp program addressing major areas of precepting skill was well received, resulted in positive feedback from operational pharmacy preceptors, and was feasible to implement at a large academic medical center.